2010
DOI: 10.1158/1940-6207.capr-09-0229
|View full text |Cite
|
Sign up to set email alerts
|

DNA Damage Drives an Activin A–Dependent Induction of Cyclooxygenase-2 in Premalignant Cells and Lesions

Abstract: Cyclooxygenase-2 (COX-2) catalyzes the rate-limiting step in the synthesis of prostaglandins. Its overexpression induces numerous tumor-promoting phenotypes and is associated with cancer metastasis and poor clinical outcome. Although COX-2 inhibitors are promising chemotherapeutic and chemopreventative agents for cancer, the risk of significant cardiovascular and gastrointestinal complications currently outweighs their potential benefits. Systemic complications of COX-2 inhibition could be avoided by specifica… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
55
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 35 publications
(60 citation statements)
references
References 44 publications
5
55
0
Order By: Relevance
“…Notably, selective knockdown of IL-6 in CAFs, but not in DCIS cells, abrogates these phenotypes. This report brings further mechanistic insights to a prior study reporting that DCIS lesions with a heightened DNA damage/activin A/ cyclooxygenase-2 (COX-2) signature were associated with a more reactive stroma (Fordyce et al 2010(Fordyce et al , 2012 and more frequent progression to invasive cancer (Kerlikowske et al 2010).…”
Section: Cafs and Disease Progressionsupporting
confidence: 64%
See 1 more Smart Citation
“…Notably, selective knockdown of IL-6 in CAFs, but not in DCIS cells, abrogates these phenotypes. This report brings further mechanistic insights to a prior study reporting that DCIS lesions with a heightened DNA damage/activin A/ cyclooxygenase-2 (COX-2) signature were associated with a more reactive stroma (Fordyce et al 2010(Fordyce et al , 2012 and more frequent progression to invasive cancer (Kerlikowske et al 2010).…”
Section: Cafs and Disease Progressionsupporting
confidence: 64%
“…Accompanying CD36 repression is the secretion of soluble factors, such as activin A, which has been implicated as a key effector in a DNA damage-inducible secretory program that acts in a cell-extrinsic fashion to generate many of the above phenotypes ( Fig. 2; Fordyce et al 2010Fordyce et al , 2012. Extending these findings, recent evidence has been provided for CD36 repression as part of a dramatic switch in fibroblast identity.…”
Section: Cafs and Disease Progressionmentioning
confidence: 90%
“…In addition, p16 Ink4a overexpression has been reported in senescent fibroblasts , in response to oxidative stress (Ksiazek et al, 2006;Quereda et al, 2007), DNA damage and changes in chromatin structure (Canepa et al, 2007;Fordyce et al, 2010). Nonetheless, a complete understanding of the signals that trigger senescence is currently lacking, and although p16 Ink4a appears to be one of the principal factors in senescence, more information is needed to ascertain the exact role of each factor in this process.…”
Section: Physiological Role Of P16 Ink4amentioning
confidence: 99%
“…Previously, we demonstrated that DNA damaging agents and/or telomere malfunction in mortal, non-tumorigenic variant human mammary epithelial cells (vHMEC) induce a DDR and activin A-dependent COX-2 expression (19). Fibroblasts from reduction mammoplasties (RMF) co-cultured with DNA-damaged vHMEC induce many genes consistent with a desmoplastic phenotype (e.g.…”
Section: Introductionmentioning
confidence: 99%